Roles and Responsibilities of the Notary in Establishment of Cooperatives - Ana Indrawati (IHSA Institute, 2023)
One aspect that is considered important that must be complied with by all legal entities, especially cooperative legal entities is the aspect of legality. To legalize it, it is necessary to draw up a deed that is ratified by an authorized official, in this case, namely a notary. The main objective of establishing a cooperative is to meet the needs of all members at the best possible level in different economic, social and political conditions. The result of research describe the role of the notary in legalizing the deed of establishment of a cooperative is that of a general official, whose main task is to draw up an authentic deed proving the special legal actions taken in the process of founding and the articles of association, and other deeds. Approval from the competent authority must be obtained in connection with cooperative activities. In conclusion, with the deed of establishment that has been legalized by a notary, it is hoped that the cooperative will become a clear legal entity and can protect its managers and membersrom various violations or irregularities that can occur in the operation of cooperatives.